Exercise-related changes in the anabolic index (testosterone to cortisol ratio) and serum amyloid A concentration in endurance and racehorses at different fitness levels - Grzędzicka, Jowita; Dąbrowska, Izabela; Malin, Katarzyna; Witkowska-Piłaszewicz, Olga (Frontiers in Veterinary Science, 2023)
Increased training loads in both human and equine athletes are generally implemented to improve their physical performance. These loads are tolerated only within appropriate training periodization with regard to recovery time. Otherwise, training overload causes failure in the systemic adaptation, which at first leads to overreaching, and progressively to overtraining syndrome (OTS). Exercise endocrinology, and anabolic/catabolic balance as an indicator of athlete performance status and OTS has continued to attract attention. In human medicine, changes in testosterone and cortisol levels, as well as the testosterone to cortisol ratio (T/C; anabolic index), are suggested to be sensitive stress markers. However, there is a lack of research investigating these parameters for use in equine sports medicine. The aim of the study was to investigate the differences in testosterone, cortisol, and T/C in response to a single training session in two types of equine sports: endurance and race, together with serum amyloid A (SAA), the main acute phase response indicator of physical effort, and the overall health status in horses. Two groups of horses were enrolled in the study: endurance (n = 12) and racehorses (n = 32) of different fitness level. Blood samples were obtained before and after the exercise. On average, T increased 2.5 times after the race training in experienced racehorses and dropped in endurance horses regardless the fitness level (p < 0.05). In endurance horses, a decrease in T/C occurred after training in inexperienced horses (p < 0.05). In racehorses, a T/C decrease occurred in the inexperienced group (p < 0.05) and an increase in the experienced (p < 0.01). In conclusion, T/C ratio was found to be a potentially reliable indicator of fitness status especially in racing horses. These findings provide insight into the physiological response of the horses to different types of exercise and the potential use of hormone levels as markers of performance and adaptation.